I'm sticking with you - Halls, Smriti; Small, Steve (Animator) (New York : Goodwin Books/Henry Holt and Company, 2020)
Wherever you're going, I'm going too. Whatever you're doing, I'm sticking with you. It's wonderful to have good friends to see you through the good times and the bad. But sometimes, friends can also be a bit . . . well . . . overbearing. A gorgeously warm, funny book about everything a friendship can be - for anyone who's ever had a friend.
"Originally published in the United Kingdom in 2020 by Simon & Schuster UK Ltd." -- Title page verso.
Keywords: Friendship -- Juvenile fiction; Bears -- Juvenile fiction; Squirrels -- Juvenile fiction; Picture books; Stories in rhyme